China’s Economic Diplomacy Towards Indonesia’s Development: A Case Study of Jakarta-Bandung High Speed Railway - Noor, Emyr Mochammad; Yiming, Song (RMPI-BRIN, 2024)
The Jakarta-Bandung High-Speed Railway (HSR) project represents a cornerstone of the evolving partnership between Indonesia and China, symbolizing the integration of strategic interests and economic diplomacy. Aligned with China's Belt and Road Initiative (BRI) and Indonesia's infrastructure development agenda, the project underscores the role of connectivity in fostering regional growth. This study examines the project’s strategic, economic, and geopolitical dimensions, emphasizing China's diplomatic strategies, including technology transfer, financial flexibility, and long-term cooperation frameworks. The HSR highlights mutual benefits, ranging from economic growth and employment creation to enhanced intercity mobility, while offering a model for bilateral collaboration. The research also explores challenges, such as political leadership transitions in Indonesia, external geopolitical pressures from the United States, and competition with Japan’s high-speed rail technologies. Despite these obstacles, the HSR demonstrates the potential of infrastructure projects to address global development goals and foster sustainable growth. By focusing on the project's implications within the BRI framework, the paper provides insights into China's aspirations for regional influence and its strategy to position itself as a global leader in high-speed rail development. Ultimately, the Jakarta-Bandung HSR serves as both a symbol and a practical example of how economic diplomacy can drive strategic partnerships, strengthen regional integration, and reshape perceptions of global power dynamics. This collaboration reflects the increasing interdependence of Indonesia and China, laying the foundation for future infrastructure initiatives and solidifying their roles in the global economic landscape.